Supply chain agility in humanitarian protracted operations. Issue 2 (1st August 2016) - L'Hermitte, Cécile; Tatham, Peter; Brooks, Ben; Bowles, Marcus
Abstract : Purpose: – The purpose of this paper is to extend the concept of agility in humanitarian logistics beyond emergency operations. Since the humanitarian logistics literature focuses primarily on emergencies and sees longer term and regular operations as being conducted in relatively stable and predictable environments, agile practices are usually not associated with humanitarian protracted operations. Therefore, this paper explores the logistics and supply chain environment in such operations in order to identify their basic features and determine if agility is an important requirement. Design/methodology/approach: – Using a case study of the United Nations World Food Programme, the authors collected and analysed qualitative and quantitative data on the characteristics of protracted operations, the risks and uncertainties most frequently encountered, their impact, and the ways that field logisticians manage contingencies. Findings: – The research demonstrates that unpredictability and disruptions exist in protracted operations. Therefore, short-term operational adjustments and agile practices are needed in order to support the continuity of humanitarian deliveries. Research limitations/implications: – Future research should focus on a wider range of humanitarian organisations and move from a descriptive to a prescriptive approach in order to inform practice. Notwithstanding these limitations, the study highlights the need for academics to broaden the scope of their research beyond emergencies and to address the specific needs of humanitarian organisations involved in longer term operations. Originality/value: – This paper is the first empirical research focusing exclusively on the logistics features of humanitarian protracted operations. It provides a more concrete and complete understanding of these operations.